Individualized Nomogram for Predicting Survival in Patients with Brain Metastases After Stereotactic Radiosurgery Utilizing Driver Gene Mutations and Volumetric Surrogates - Zhou, Cheng; Shan, Changguo; Lai, Mingyao; Zhou, Zhaoming; Zhen, Junjie; Deng, Guanhua; Li, Hainan; Li, Juan; Ren, Chen; Wang, Jian; Lu, Ming; Zhang, Liang; et al. (Frontiers in Oncology, 2021)
It is well-known that genomic mutation plays a significant role in patients with NSCLC for personalized treatment. Given the increasing use of stereotactic radiosurgery (SRS) for brain metastases (BM), there is an emerging need for more precise assessment of survival outcomes after SRS. Patients with BM and treated by SRS were eligible. Primary endpoint was overall survival (OS). Cox models were used to identify independent prognostic factors. Survival predictive nomogram was developed and evaluated by Concordance-index (C-index), area under the curve (AUC) and calibration curve. From January 2016 to December 2019, a total of 356 BM patients were eligible. Median OS was 17.7 months (95%CI 15.5-19.9) and actual OS at 1- and 2-years measured 63.2% and 37.6%, respectively. Nomogram for OS was developed by incorporating four independent prognostic factors: Karnofsky Performance Score , cumulative tumor volume, gene mutation status and serum lactate dehydrogenase . The nomogram was validated in a separate cohort demonstrated a well calibration and good discriminative ability (C-index=0.780, AUC=0.784). The prognostic accuracy of the nomogram (0.792) was considerably enhanced compared with classical prognostic indices, i.e., GPA (0.708), RPA (0.587) and SIR (0.536). Kaplan-Meier curves showed significant difference of OS among stratified low-, median- and high-risk groups (P < .001). In conclusion, we developed and validated an individualized prognostic nomogram by integrating physiological, volumetric, clinical chemistry and molecular biological surrogates. This nomogram, should be validated by independent external study, has a potential to facilitate more precise risk-stratifications to guide personalized treatment for BM.